The Utilization Management of Path Analysis Methods to Improve Quality in Writing Research Reports at Higher Education - Dhaniarti, Iswachyu; Handayani, Indri; Bachri, Egi Wijatriana (Pandawan, 2018)
In writing a research report requires good management, starting from the start to the end pages must be neatly arranged in accordance with existing rules. In managing the research report method, a researcher can use a variety of methods available, tailored to what he studies. This study discusses the introduction of path analysis, the notion of path analysis, which is a method for studying the direct effects or indirect effects of hypothesized variables as the causes of the effects of variables needed in research, characteristics of path analysis and terms in path analysis . There are 2 (two) completion of path analysis, namely with simple correlation, completion of path analysis with linear regression. Literary research research methods were used in this study to add insight to researchers regarding writing management. With this research, it is expected to be able to help students who are compiling reports in higher education, and can improve the quality of management of research reports using path analysis methods.